APLIKASI MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS ANDROID MATERI SISTEM EKSKRESI MANUSIA UNTUK SISWA KELAS XI SMA/MA - Adi Riyadi (Pixel :Jurnal Ilmiah Komputer Grafis, 2017)
In order to increase student interest in learning, increase grades and facilitate the understanding of biology subjects on the material of the human excretion system class XI Science. From a number of smarphone users in Indonesia, it turns out that most of the people are only intended for telephone, short message service (SMS), playing songs / videos, accessing social networks (facebook, twiter, BBM, Line, WhatsApp) and many playing games including students in high school. Negeri 2 Mranggen. The author uses data collection research methods including observation, interviews, questionnaires, R&D product development methods, prototype methods and object-oriented approaches. The equipment used in designing this system uses UML modeling. Use Case Diagrams include, Activity Diagrams, Class Diagrams, and Sequence Diagrams and the software used by the author is Android Development Tools (ADT) and MySQL as a database. Mobile learning media application is expected to help facilitate the needs of students to learn the material of the human excretion system online at any time without any place and time restrictions.